Design of Reference Phantom for Quality Control of Conventional X-ray Radiography Units in Port Sudan - Abdallah, Yousif Mohamed Y.; Zaki, Wail; Ahmadoun, Babeker; Musa, Abuobeada (British Journal of Healthcare and Medical Research, 2020)
The Quality Control (QC) system, based on simple, cheap equipment and minimum personnel time, enables a resource-limited facility and staff to control the fundamental components of the imaging process on a low cost basis. Quality Assurance (QA) is a product or service quality management program. Customer reviews, capacity building and quality control can also be included. Quality control requires specific measures for ensuring measurable process-related aspects of product output or for the delivery of services within a given limit. Research was conducted at the Medical Physics Department of Red Sea University. The main objective of this work was to boost quality assurance rays. The imagination is more user-friendly and produces better results than a person or object. Phantoms, including fluoroscopy or x-rays, and certain image quality measurements have been used in x-rays imaging. The manufactured phantom in this study showed high precision in different QC tests.